Maintaining the Digital Public Space: Communication Ethics and Regulatory Challenges in the TikTok Era - Rustanta, Agustinus; Dwi Putranto, Suryo; Huang, Paticia (Jurnal Komunikasi, 2025)
Social media has undergone a transformation from a mere entertainment platform into a digital public sphere that facilitates broad political and social expression. TikTok, as one of the most popular short-video platforms, has become a powerful medium for voicing criticism against public figures, including Indonesian President Joko Widodo. The rise of hate speech on TikTok signals a crisis in communication ethics and the weakness of digital content regulation in Indonesia. While prior research has addressed political polarization in social media, few studies have specifically examined how theatrical content and hate narratives are disseminated on TikTok as a public space lacking editorial gatekeepers. This study aims to explore forms of hate speech targeting President Jokowi on TikTok and to analyze the ethical and regulatory gaps that enable its circulation. Employing a qualitative approach, data were collected through in-depth observation of eight TikTok videos that featured theatrical, provocative, and symbolically aggressive elements. The findings reveal that hate content is expressed through verbal insults, visual symbolism, and the manipulation of political issues such as nepotism, ethical violations, and electoral law revisions. These results highlight the need to reformulate theories of the public sphere and communication ethics in the digital age. The study recommends the development of more adaptive regulatory systems and the strengthening of digital literacy among users. Theoretically, it contributes to the expansion of digital public sphere theory, mediation theory, and social identity theory within the context of algorithmic virality.